Application of aromatherapy to treat PONV in patients post neurosurgery - Kurnia, Anna; Sitorus, Ratna; Kariasa, I Made; Mulyatsih, Enny (University of Muhammadiyah Semarang, 2024)
Postoperative nausea and vomiting (PONV) stands as one of the most prevalent complications within the initial 24 hours following surgery, potentially extending the Length of Stay (LOS) and incurring elevated financial burdens for patients in hospital settings. Aromatherapy emerges as a non-pharmacological approach for alleviating PONV symptoms. This case study aims to evaluate PONV severity and manage symptoms in neurosurgical patients utilizing a nursing process approach. Employing a case study design integrated with a nursing process approach, this study was conducted. The inclusion criteria were respondents aged 18 or older, American Society of Anesthesiologist (ASA) I or II classification, undergoing neurosurgery under general anaesthesia, willing to participate, conscious (GCS: 14-15), with a healthy sense of smell, and PONV scores of 1 or 2. Exclusion criteria comprised discharged or deceased patients, absence of PONV, respiratory issues like asthma/COPD, odor allergies, and severe post-surgical complications. Dropout criteria included sudden emergencies or alternative interventions during PONV assessments. Results showed 4 patients with PONV 1 scores and 6 with PONV 2 scores before aromatherapy. After aromatherapy, 6 patients had PONV 0 scores, 2 had PONV 1 scores, and 2 had PONV 2 scores. Findings underscore alterations in PONV scores pre- and post-aromatherapy administration, highlighting the potential of this evidence-based nursing intervention to enhance patient comfort and mitigate postoperative complications in neurosurgical settings.